Evaluation of the effectiveness of air pollution control measures in Hong Kong. (January 2017) - Lyu, X.P.; Zeng, L.W.; Guo, H.; Simpson, I.J.; Ling, Z.H.; Wang, Y.; Murray, F.; Louie, P.K.K.; Saunders, S.M.; Lam, S.H.M.; Blake, D.R.
Abstract: From 2005 to 2013, volatile organic compounds (VOCs) and other trace gases were continuously measured at a suburban site in Hong Kong. The measurement data showed that the concentrations of most air pollutants decreased during these years. However, ozone (O3 ) and total non-methane hydrocarbon levels increased with the rate of 0.23 ± 0.03 and 0.34 ± 0.02 ppbv/year, respectively, pointing to the increasing severity of photochemical pollution in Hong Kong. The Hong Kong government has ongoing programs to improve air quality in Hong Kong, including a solvent program implemented during 2007–2011, and a diesel commercial vehicle (DCV) program since 2007. From before to after the solvent program, the sum of toluene, ethylbenzene and xylene isomers decreased continuously with an average rate of −99.1 ± 6.9 pptv/year, whereas the sum of ethene and propene increased by 48.2 ± 2.0 pptv/year from before to during the DCV program. Despite this, source apportionment results showed that VOCs emitted from diesel exhaust decreased at a rate of −304.5 ± 17.7 pptv/year, while solvent related VOCs decreased at a rate of −204.7 ± 39.7 pptv/year. The gasoline and liquefied petroleum gas vehicle emissions elevated by 1086 ± 34 pptv/year, and were responsible for the increases of ethene and propene. Overall, the simulated O3 rate of increase was lowered from 0.39 ± 0.03 to 0.16 ± 0.05 ppbv/year by the solvent and DCV programs, because O3 produced by solvent usage and diesel exhaust related VOCs decreased (p < 0.05) by 0.16 ± 0.01 and 0.05 ± 0.01 ppbv/year between 2005 and 2013, respectively. However, enhanced VOC emissions from gasoline and LPG vehicles accounted for most of the O3 increment (0.09 ± 0.01 out of 0.16 ± 0.05 ppbv/year) in these years. To maintain a zero O3 increment in 2020 relative to 2010, the lowest reduction ratio of VOCs/NOx was ∼1.5 under the NOx reduction of 20–30% which was based on the emission reduction plan for Pearl River Delta region in 2020. Graphical abstract: Highlights: NMHCs and O3 increased in Hong Kong from 2005 to 2013. Solvent and DCV programs were effective in reducing VOCs and O3 . LPG and gasoline vehicles made increasing contributions to VOCs and O3 . More stringent measures should be taken to control VOCs emissions. Abstract : Both the solvent and DCV programs were effective on the reduction of VOC emissions and O3 production.